2022
DOI: 10.3390/cancers14030724
|View full text |Cite
|
Sign up to set email alerts
|

CONUT Score: A New Tool for Predicting Prognosis in Patients with Advanced Thyroid Cancer Treated with TKI

Abstract: (1) Background: The Controlling Nutritional Status (CONUT) score is an immuno-nutritional screening tool based on serum albumin, total cholesterol, and lymphocyte count. The aim of the study was to assess the CONUT score as a potential prognostic factor of response to therapy in patients with advanced thyroid cancer treated with tyrosine kinase inhibitors (TKIs). (2) Methods: We retrospectively evaluated 42 metastatic thyroid cancer patients (54.8% female). The median age at the time of TKI treatment was 69 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Finally, CONUT consists of lymphocytes and albumin together with cholesterol, so it is not difficult to understand that CONUT is associated with the prognosis of cancer patients. The coefficient of CONUT in NMRS was 0.354, which is consistent with previous findings ( 52 ).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, CONUT consists of lymphocytes and albumin together with cholesterol, so it is not difficult to understand that CONUT is associated with the prognosis of cancer patients. The coefficient of CONUT in NMRS was 0.354, which is consistent with previous findings ( 52 ).…”
Section: Discussionsupporting
confidence: 92%
“…The CONUT score is an index related to ALB concentration, lymphocyte count, and TC concentration. Studies have shown that the CONUT score is strongly correlated with the survival rate of patients with thyroid cancer; it is also an independent risk factor for lung cancer prognosis[ 25 , 43 ]. NPS is an index related to serum ALB concentration, TC concentration, LMR, and NLR and has been proven to be a predictor of OS in a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that CONUT score is a prognostic item in patients with MDS. Although the underline mechanism of action and how high CONUT score indicates true undernutrition or cachexia are still unclear, but it becomes a consensus that CONUT score is a useful tool ( 19 21 ), which can be quickly and accurately detected in peripheral blood test at diagnosis.…”
Section: Discussionmentioning
confidence: 99%